Tinnitus Treatment with Precise and Optimal Electric Stimulation: Opportunities and Challenges - Zeng, Fan-Gang (Curr Opin Otolaryngol Head Neck Surg, 2015)
PURPOSE OF REVIEW: Electric stimulation is a potent means of neuromodulation that has been used to restore hearing and minimize tremor, but its application on tinnitus symptoms has been limited. We examine recent evidence to identify the knowledge gaps in the use of electric stimulation for tinnitus treatment. RECENT FINDINGS: Recent studies using electric stimulation to suppress tinnitus in humans are categorized according to their points of attacks. First, non-invasive, direct-current stimulation uses an active electrode in the ear canal, tympanic membrane or temporal scalp. Second, inner ear stimulation uses charge-balanced biphasic stimulation by placing an active electrode on the promontory or round window, or a cochlear implant array in the cochlea. Third, intraneural implants can provide targeted stimulation of specific sites along the auditory pathway. Although these studies demonstrated some success in tinnitus suppression, none established a link between tinnitus suppression efficacy and tinnitus-generating mechanisms. SUMMARY: Electric stimulation provides a unique opportunity to suppress tinnitus. Challenges include matching electric stimulation sites and patterns to tinnitus locus and type, meeting the oftentimes-contradictory demands between tinnitus suppression and other indications, such as speech understanding, and justifying the costs and risks of electric stimulation for tinnitus symptoms.